Open Data and Civic Apps: First-Generation Failures, Second-Generation Improvements. - MELISSA LEE; ALMIRALL, ESTEVE; WAREHAM, JONATHAN (Communications of the ACM, 2016)
The article looks at mobile applications (apps) which use publicly-available government data. The authors investigate why the first generation of civic apps developed through the open data movement did not enjoy widespread popularity. It is suggested that loose governance and limited knowledge transfer inhibited the success of these first apps, while stronger management and attention to third-party motivations enhanced the second generation of apps. Other topics include development competitions and cities' advertising of apps.